An Evaluation of the Assessment System in the 7th-Grade MTS Arabic Textbook Based on the Principles of Henry Douglas Brown - Arini Lutfi Solihah; Nasokah Nasokah; Ashief El Qorny (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to evaluate the assessment system in the Arabic textbook for 7th-grade MTs, Semester 2, published by the Ministry of Religious Affairs, based on the principles of evaluation according to H. Douglas Brown. The evaluation principles used include practicality, reliability, validity, authenticity, and washback. This study employs a qualitative approach using a descriptive research design through library research. The primary data source in this study is the Arabic textbook for Grade 7 MTs, Semester 2, while secondary data was obtained from various relevant literature. Data collection was conducted through documentary analysis, while data analysis utilized content analysis. The results indicate that the evaluation system in the textbook is quite good and systematic.Assessments are presented in both formative and summative formats and include a variety of question types, such as multiple-choice, short-answer, matching, translation, sentence construction, true-false, and fill-in-the-blank. The assessment also covers the four language skills: listening, speaking, reading, and writing. Based on Brown’s principles, the assessment in this textbook meets the criteria of practicality, validity, and authenticity. The reliability aspect shows good potential but remains dependent on the teacher’s consistency in administration and scoring. Meanwhile, the washback aspect has the potential to positively impact learning, although this still requires validation through field research. Thus, the Arabic textbook for Grade 7 MTs, Semester 2, is suitable for use as teaching material and a learning assessment tool; however, it still requires refinement in the scoring guidelines, teaching methods, and the strengthening of communicative exercises.